Optimization of osteoporosis and osteopenia management among renal transplant recipients - Mohammed K. Afifi; Ahmed S. Kenawy; Heba H. El Demellawy; Amany A. Azouz; Torki Al-Otaibi; Osama Gheith; Mohamed Abd ElMonem; Mohamed S. AbdElhalim; Raghda R. S. Hussein (SpringerOpen, 2021)
Abstract Background Osteoporosis and osteopenia occur frequently in renal transplant recipients due to long-term use of immune-suppressants including corticosteroids. Previous treatment options like bisphosphonates had acceptable but rather unsatisfactory results after transplant. The aim of the current study is to directly compare the efficacy of denosumab and oral ibandronate in late RTR with low bone mineral density. Results The study was conducted Iin Hamed Al-Essa Kidney transplant center, Kuwait, in 2020. The data of 52 denosumab and 48 ibandronate patients were collected at the baseline and after one year of treatment. Spine and hip T-score readings, side effects, and other laboratory results were analyzed to evaluate the use of both medications. The mean number of months after transplant was 25 (± 13.9) months. After one year of treatment, denosumab alleviated both spinal osteoporosis and osteopenia T-score values from −3.13 to −2.4 (p = 0.008) and from −1.9 to −1.5 (p = 0.015), respectively. Besides, it reduced hip osteoporosis and osteopenia insignificantly from −3.45 to −3.1 and from −1.5 to −1.3, respectively (p > 0.05). Ibandronate improved spinal osteopenia from −1.6 to −1.55 (p = 0.97) and failed to show any positive impact on other sites; the spinal osteoporosis changed from −2.8 to −3 and hip osteoporosis and osteopenia changed from −3.1 to −3.12 and from −1.4 to −1.45, respectively (p > 0.05). The use of ibandronate was more associated with gastrointestinal tract (GIT) side effects, while hypocalcemia episodes were significantly higher in the denosumab group. Conclusion Denosumab improved both spinal and hip T-score values in comparison with ibandronate in RTR. Close monitoring is required for denosumab patients to prevent the associated hypocalcemia. Graphical Abstract